2019
DOI: 10.1123/japa.2018-0259
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Phase Angle Are Related With Muscle Quality Index After Resistance Training in Older Women

Abstract: The aim of this study was to analyze the association between muscle quality index (MQI) and phase angle (PhA) after a program of progressive resistance training (RT) in older women. Sixty-six older women with previous RT experience (68.8 ± 4.6 years, 156.6 ± 5.3 cm, 66.0 ± 13.0 kg, and 26.7 ± 4.6 kg/m2) underwent 12 weeks of RT (3 ×/week, eight exercises, and 10–15 repetition maximum). Anthropometry, muscular strength (one-repetition maximum tests), and body composition (dual-energy X-ray absorptiometry and sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 27 publications
4
40
0
Order By: Relevance
“…It has been reported that phase angle was significantly associated with the muscle quality index in older women and it could be improved after resistance training. 16 Furthermore, phase angle has been proved to be associated with handgrip strength but not with sarcopenia, 15 suggesting phase angle may reflect muscle status from another side different from muscle mass. Another recently published study supported our result which revealed older adults with lower phase angles were more likely to experience prospective falls compared with those with normal-high phase angles, 20 although the significance of the overall phase angle was explored in their research rather than the individual trunk phase angle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that phase angle was significantly associated with the muscle quality index in older women and it could be improved after resistance training. 16 Furthermore, phase angle has been proved to be associated with handgrip strength but not with sarcopenia, 15 suggesting phase angle may reflect muscle status from another side different from muscle mass. Another recently published study supported our result which revealed older adults with lower phase angles were more likely to experience prospective falls compared with those with normal-high phase angles, 20 although the significance of the overall phase angle was explored in their research rather than the individual trunk phase angle.…”
Section: Discussionmentioning
confidence: 99%
“…BIA can also measure phase angle which to some extent can reflect the functional status of muscles. [14][15][16] The potential association of phase angle of trunk muscle with the chance of femoral neck fracture has not been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it has been shown that obese women with a low PA tertile have high fat mass with high levels of glucose and higher cardiovascular risk factors [18]. On the other hand, in relation to muscle function, improvements in PA are also associated with increases in strength, in particular that of hand grip (HS) [19,20]. In this regard, HS and muscle strength, indicators of muscle quality, have shown to be more significant than muscle mass in estimating mortality risk [21].…”
Section: Introductionmentioning
confidence: 99%
“…The aging-associated alterations in body composition, manifested by reduction of skeletal muscle mass and increased body fat, may influence BIVA parameters resulting in PhA decreases [8][9][10][11][12]. In contrast, exercise practice promotes positive changes in BIVA and PhA, followed by benefits on psychological, cognitive, and physical aspects, hydration, nutritional status, muscle function, and quality of life in the elderly [11][12][13][14][15][16][17][18][19][20]. Resistance training (RT) is one of the potential strategies to reverse the adverse effects of aging on cellular integrity and function, improve BIA parameters, and induce changes in the cellular volume of skeletal muscle tissue and cell membrane potential [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, exercise practice promotes positive changes in BIVA and PhA, followed by benefits on psychological, cognitive, and physical aspects, hydration, nutritional status, muscle function, and quality of life in the elderly [11][12][13][14][15][16][17][18][19][20]. Resistance training (RT) is one of the potential strategies to reverse the adverse effects of aging on cellular integrity and function, improve BIA parameters, and induce changes in the cellular volume of skeletal muscle tissue and cell membrane potential [8][9][10][11][12][13]. However, despite some recent and preliminary results [11,[21][22][23], the dose-response relationship regarding specific RT variables (e.g., training period, frequency, intensity, volume, training system) on bioelectrical parameters is unclear.…”
Section: Introductionmentioning
confidence: 99%